Shear Strength Deterioration of Compacted Residual Soils under a Wind Turbine due to Drying-Wetting Cycles and Vibrations - Yan-Ming Zhou; Zong-Wei Deng; Zi-Jian Fan; Wen-Jie Liu (Advances in Civil Engineering)
The soil beneath a wind turbine withstands not only environmental impacts but also continuous vibrations transmitted from the superstructure. This paper presents an experimental study of the deterioration characteristics of shear strengths of residual soils affected by drying-wetting cycles and continuous vibrations. A series of triaxial tests were performed on compacted residual soil specimens after various drying-wetting cycles and vibrations. The influences of drying-wetting cycles and vibrations on the shear strengths of residual soils with different compaction degrees were analyzed. The results demonstrate that the shear strength and cohesion of compacted residual soils decreased as the number of drying-wetting cycles increased, and they tended to be stable after three drying-wetting cycles. The angle of internal friction decreased linearly with the reduction of compaction degree but was generally not affected by drying-wetting cycles. The shear strength of compacted residual soils also decreased because of continuous vibrations. After 10000 vibrations, the strength was stabilized gradually. Both the cohesion and angle of internal friction showed dynamic attenuation phenomenon. Finally, a modified Mohr–Coulomb strength equation considering the effects of drying-wetting cycles and vibrations was established. This equation could be used to predict the shear strength of compacted residual soils and further estimate the embedded depth of wind turbine foundations.